Becoming an Engaged Department: Scaffolding Community-Based Learning Into the Hospitality and Tourism Management Curriculum. Issue 3 (3rd July 2019) - Tuma, Lorie A.; Sisson, Lisa G.
ABSTRACT: Universities are embedding and formalizing community-based learning opportunities into their ethos, evolving toward a model of working with community partners in mutually beneficial long-term relationships. This process is being undertaken in pursuit of enriched scholarship, enhanced teaching and learning, and the development of educated citizens with strong democratic values and civic responsibility who can address critical societal issues and contribute to the public good. This article explores one university's hospitality and tourism management department's integrated approach to formally adopting a scaffolded curriculum. These programmatic changes provide a model for becoming an engaged department and partnering with the industry to achieve mutually beneficial outcomes.